Narratives of communities on the challenges of inclusive education and equity in Latin America - Calderón-Almendros, Ignacio; Ainscow, Mel (My University, 2024)
For more than 6 years, we have developed different participatory and collaborative research processes committed to the voices of students, families and teachers involved in inclusive education and equity in seven Latin American countries (Calderon et al., 2020; Ainscow et al., in press). The dialogue processes generated have meant great advances in the development of the critical capacity of the participants to understand their complex realities, first in large events that allowed analysis and proposals to be shared at the system level, and later in school communities, which would facilitate transformations at the school and classroom levels. In all these processes, the participants were generating new theoretical tools, more inclusive thoughts, and proposals more appropriated to the needs of their own communities, taking especially into account the emoCons and knowledge of the most oppressed people. All of this has allowed a critical analysis of their situations, and the construction of their own theories of change. References: Calderón-Almendros, I., Ainscow, M., Bersanelli, S., & Molina, P. (2020). Educational inclusion and equity in Latin America: an analysis of the challenges. Prospects: Comparative Journal of Curriculum, Learning, and Assessment, 49(3), 169-186. https://doi.org/10.1007/s11125-020-09501-1 Ainscow, M., Calderón-Almendros, I., Duk, C., & Viola, M. (in press). Using professional development to promote inclusive education in Latin America: possibilities and challenges. Professional Development in Education.
Keywords: Educación inclusiva; Inclusive education